PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE CARD SORT (KARTU SORTIR) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON DI KELAS X SMAN 5 PEKANBARU - Mesy Witari; R.Usman Rery; Sri Haryati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Research on the strategy of active learning with Card Sort type has been conducted with the aim to know the improvement in student achievement on the subject of Hydrocarbon material at class X SMAN 5 Pekanbaru. This research is experimental research with randomized control group pretest-posttest design. Time of data collection was conducted on 26 April – 25 May 2016. The sample consisted of two classes. Experimental Class is the class that active learning with card sort type had been given, and Control Class is the class with no active learning with card sort type. Analyze of data used t-test formula. Result of data processing obtained tcount>ttable is 4,51> 1,67 and influence of this strategy for improve student achievement is 23,04%. So, the conclude is the application of active learning with card sort type can improve student achievement on the topic of Hydrocarbon material at class X SMAN 5 Pekanbaru.Keyword: Active Learning With Card sort Type, study achievement, Hydrocarbon